Stylistic Analysis of the Representation of Trauma and Female Identity in the Poems “Daddy” and “Lady Lazarus” - Fadya Putri Pratiwi (Critical Review of English-Arabic World Journal, 2025)
This research is motivated by the strong representation of trauma and the construction of female identity in Sylvia Plath's poems, which are often discussed in literary studies, literary psychology, and even feminist criticism. This study aims to analyse how stylistic elements in the poems ‘Daddy’ and ‘Lady Lazarus’ are used to present traumatic experiences, female identity crises, and resistance to patriarchal domination. The method used is descriptive qualitative through in-depth reading of diction, metaphors, imagery, repetition, and symbols enriched by trauma theory, literary psychology, and stylistics. The results of this study are expected to show that the poem ‘Daddy’ reveals deep trauma through extreme metaphors such as Nazis, death, and wounds, while the poem ‘Lady Lazarus’ describes the resurrection of female characters through irony, repetition, and body imagery arranged as symbols of the healing process. Both poems show that poetic language becomes a space for the poet to voice traumatic experiences while simultaneously reconstructing the identity of women who were once constrained by the patriarchal system.